Dimensions of national innovation culture in Croatia. Content validity of Hofstede’s dimensions - Lažnjak, Jasminka (2011)
How important is the role of innovation supportive culture for innovation on the level of society? Faced with the challenge to increase the level of innovation in science and technology many societies have developed national innovation system as a form of public policy programs that would foster innovation. If innovative culture is crucial for the adoption and development of new technologies it is of great importance to explore the concept and possibly find out which type of culture is more innovative than others. In the paper are presented the results of the first empirical study of innovation culture in Croatia based on survey on the representative sample of Croatian population. Drawing on Hofstede’s concept of dimensions of national culture Croatian national innovation culture is operationalized as set of value orientations and norms (uncertainty avoidance, individualism, masculinity - femininity, long-term or short-term orientation, and power distance). Four scales based on Hofstede’s dimensions were constructed which mainly supports the content validity of his concept. The scales could be used to measure differences between groups and regions in innovative capacity. The analysis shows the presence of multiple dimensions of innovation culture in Croatia that might hinder innovation capacity but this doesn’t necessary lead to the conclusion that we can identify one type culture elements as the only model for strengthening the innovative culture.
Projekt MZOS
Projekt MZOS
ENG